A core outcome set for school-based physical activity interventions: an international consensus. (20th October 2021) - Ram, B; Foley, K; van Sluijs, E; Hargreaves, D; Viner, R; Saxena, S
Abstract: Background: Studies of school-based physical activity interventions vary in the outcomes they measure. This prevents comparisons of results to establish impacts. We aimed to develop a core outcome set agreed by key stakeholders for future studies of school-based physical activity interventions. Methods: We used a modified-Delphi consensus method. First, we conducted a systematic review to identify outcomes measured in relevant studies and listed these in a Delphi survey. Next, we recruited key stakeholders to complete 2 survey rounds: Round 1 was to rate each outcome from 'not important' to 'critical', and Round 2 was to re-rate the outcomes based on feedback from Round 1. Outcomes rated 'critical' by 70% of stakeholders (i.e., reaching consensus) were highlighted. Then, using the full list of outcomes, we conducted a children's workshop to include their views. Finally, we held a stakeholder meeting to discuss results and agree consensus. Results: We identified 50 outcomes from the systematic review. Sixty-five stakeholders (16 educators, 13 health professionals, 12 parents, 24 researchers) representing 9 countries completed both survey rounds; 13/50 outcomes reached consensus. Children (n = 16) identified 8 outcomes of importance; 3 were consistent with the survey results. Stakeholders attending the meeting (n = 13) reached consensus on 14 outcomes to be included in the core outcome set: fitness, physical activity intensity, energy, sleep, diet, happiness, stress, depression, anxiety, wellbeing, self-esteem, enjoyment, concentration, and focus. These core outcomes were reviewed and agreed by all 65 stakeholders. Conclusions: Our core outcome set agreed by international stakeholders includes physical and mental health, and cognitive function. We recommend its use in future studies of school-based physical activity interventions. Findings from future studies can be compared and combined which will be relevant to public health policy makers and educators. Key messages: School-based physical activity interventions should measure physical and mental health, and cognitive function. Wide use of this core outcome set will enable findings to be compared and combined.